Recommendation to include hydroxyethyl (meth)acrylate in the British baseline patch test series. (1st October 2019) - Rolls, S.; Chowdhury, M.M.; Cooper, S.; Cousen, P.; Flynn, A.M.; Ghaffar, S.A.; Green, C.M.; Haworth, A.; Holden, C.; Johnston, G.A.; Naidoo, K.; Orton, D.I.; et al.
Summary: Background: (Meth)acrylates are potent sensitizers and a common cause of allergic contact dermatitis (ACD). The frequency of (meth)acrylate ACD has increased with soaring demand for acrylic nails. A preliminary audit has suggested a significant rate of positive patch tests to (meth)acrylates using aimed testing in patients providing a clear history of exposure. To date, (meth)acrylates have not been routinely tested in the baseline patch test series in the U.K. and Europe. Objectives: To determine whether inclusion of 2‐hydroxyethyl methacrylate (2‐HEMA) 2% in petrolatum (pet.) in the baseline series detects cases of treatable (meth)acrylate ACD. Methods: During 2016–2017, 15 U.K. dermatology centres included 2‐HEMA in the extended baseline patch test series. Patients with a history of (meth)acrylate exposure, or who tested positive to 2‐HEMA, were selectively tested with a short series of eight (meth)acrylate allergens. Results: In total 5920 patients were consecutively patch tested with the baseline series, of whom 669 were also tested with the (meth)acrylate series. Overall, 102 of 5920 (1·7%) tested positive to 2‐HEMA and 140 (2·4%) to at least one (meth)acrylate. Had 2‐HEMA been excluded from the baseline series, (meth)acrylate allergy would have been missed in 36 of 5920 (0·6% of all patients). The top (meth)acrylates eliciting a positive reaction were 2‐HEMA ( n = 102, 1·7%), 2‐hydroxypropyl methacrylate ( n = 61, 1·0%) and 2‐hydroxyethyl acrylate ( n = 57, 1·0%). Conclusions: We recommend that 2‐HEMA 2% pet. be added to the British baseline patch test series. We also suggest a standardized short (meth)acrylate series, which is likely to detect most cases of (meth)acrylate allergy.